Removal of organic matter and toxicity in an upflow immobilized biomass anaerobic reactor treating hospital wastewater: preliminary evaluation (2013)
The aim of this research was to evaluate the performance of an Upflow Immobilized Biomass Anaerobic Reactor (UIBAR) treating real hospital wastewater. The organic matter removal and the toxicity were assessed through COD, UV254nm and the measure of the growth inhibition of onion roots (Allium cepa L). The results show that the biological process was stable during the 287 days of continuous operation; the mean value of the IA/PA relation was 1.21±0.08, indicating that there was no acid accumulation in the system. However, the efficiency of reduction of COD, 56±15% and UV254nm, 21±36%, is not quite representative. The toxicity was reduced in by 50%. Therefore, it is necessary to continue with the removal of organic matter to combine the anaerobic process with other processes such as an advanced oxidation process. The capacity of the anaerobic immobilized process to remove the compounds that produce toxicity was verified.